Metals, microbes, and minerals the biogeochemical side of life - Kroneck, Peter M. H.; Sosa Torres, Martha E. (Metal ions in life sciences ;, 2021)
Metal Ions in Life Sciences links coordination chemistry and biochemistry in their widest sense and thus increases our understanding of the relationship between the chemistry of metals and life processes; in fact, it is an old wisdom that metals are indispensable for life. The series reflects the interdisciplinary nature of Biological Inorganic Chemistry and coordinates the efforts of scientists in numerous interconnecting research fields. --